Amoeboid-like migration ensures correct horizontal cell layer formation in the developing vertebrate retina - Amini, Rana; Bhatnagar, Archit; Schlüßler, Raimund; Möllmert, Stephanie; Norden, Caren; Guck, Jochen (eLife, 2022)
Migration of cells in the developing brain is integral for the establishment of neural circuits and function of the central nervous system. While migration modes during which neurons employ predetermined directional guidance of either preexisting neuronal processes or underlying cells have been well explored, less is known about how cells featuring multipolar morphology migrate in the dense environment of the developing brain. To address this, we here investigated multipolar migration of horizontal cells in the zebrafish retina. We found that these cells feature several hallmarks of amoeboid-like migration that enable them to tailor their movements to the spatial constraints of the crowded retina. These hallmarks include cell and nuclear shape changes, as well as persistent rearward polarization of stable F-actin. Interference with the organization of the developing retina by changing nuclear properties or overall tissue architecture hampers efficient horizontal cell migration and layer formation showing that cell-tissue interplay is crucial for this process. In view of the high proportion of multipolar migration phenomena observed in brain development, the here uncovered amoeboid-like migration mode might be conserved in other areas of the developing nervous system.
CRIS-Team Scopus Importer:2022-08-03
Keywords: amoeboid cell migration; developmental biology; horizontal cells; neuronal lamination; neuronal migration; retina; zebrafish